Consumer Willingness to Pay (WTP) Analysis of Salt Eggs Products in Brebes District - Wulandari, Hilda Kumala; Dumadi, Dumadi (Budapest International Research and Critics University, 2022)
Different perceptions of salted egg prices are one of the triggers for the decline in selling levels for producers, therefore in determining the selling price it is important to know how much consumers are willing to pay or willingness to pay (WTP) to buy salted egg products. Then there are factors that affect consumers' willingness to pay including income, product prices, product quality and product safety. This research was conducted to determine the characteristics of Brebes salted egg consumers, determine the average maximum price of salted eggs that consumers are willing to pay, analyze the factors that influence consumers' willingness to pay for Brebes salted egg products. This research was conducted in Brebes Regency using 100 respondents who were selected by accidental sampling method. Methods of data analysis using descriptive analysis, contingent valuation method (CVM) and multiple linear regression analysis. The results of the study stated that the characteristics of salted egg consumers who are willing to pay more in Brebes Regency are dominated by consumers aged 30 to 40 years, with a bachelor's education background, working as an entrepreneur, with an income level of Rp. 1.000.0000, up to Rp. 5,000,000, the average maximum price that Brebes salted egg consumers are willing to pay is IDR 377 per egg. The factors that influence the willingness of consumers to pay for salted egg products are income and quality of Brebes salted egg products.